The Negation Jangan from a Lexical Functional Perspective - Pasaribu, Truly Almendo (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2013)
This paper is an investigation into the properties of the negation jangan in the framework of Lexical-Functional Grammar. The analysis shows that the negation jangan can negate verbs functioning as predicate in a sentence. It follows both transitive and intransitive verbs. The constituent that fills the position in the subject is defined by the voice of the sentence. If it is in the active voice, the subject is the second person pronoun. On the other hand, if the word jangan negates passive voice, the subject is not restricted. It is possible in Indonesian sentence to have double negation because the negative adverb jangan can negatea negation tidak. It also follows adjectives, adverbs, nouns and clauses. Thenegation jangan also has a different grammatical construction when it precedesthe preposition sampai. The subject following jangan sampai is not restricted asthe subject following jangan sampai is in active voice. The word jangan can befronted to modify the whole clause.